Acid mine drainage (AMD) contamination in coal mines and the need for extensive prediction and remediation: a review - Theophilus Ile Ojonimi; Ilemona C Okeme; Tina Phiri Chanda; Eneojo Godwin Ameh (Brawijaya University, 2021)
Globally, the major source of environmental pollution as a result of mineral exploitation and processing is acid mine drainage (AMD). AMD refers to outflowing streams of acidic constituents from pyrite-bearing ore mines. The exposure of pyrite (FeS2) in coal waste dumps to atmospheric oxygen and water in the presence of microbial communities promotes the formation of sulphuric acid which leaches out the inherent heavy metals into the mine discharge, a phenomenon called pyrite oxidation. AMDs are usually characterized by a convoy of toxic heavy metals, most of which are transition elements (copper, nickel, zinc, etc.) and arsenic at concentrations higher than the limits permitted by environmental regulations. The impact of this acidic discharge from coal mines on downstream/underground waters and farm lands within the corresponding mining zones have been severally reported by previous researchers, but not so much have been discussed on extensive prediction and remediation. It is in view of this that the current paper reviews the need for extensive prediction and remediation approach for coal mines under the following subheadings; General introduction, AMD sources identification, representative sampling, adoption of a prediction model, determination of AMD potential and quality via static and kinetic tests and the development of an economically sustainable remediation strategy. It is thought that this article would be useful to academia as well as policy makers that are responsible for the development and implementation of environmental regulations in coal mines.